Modeling Soil Wind Erosion From Agroecological Classes of the Pacific Northwest in Response to Current Climate. Issue 2 (22nd January 2020) - Pi, Huawei; Huggins, David R.; Abatzoglou, John T.; Sharratt, Brenton
Abstract: Soil wind erosion is a major concern of the agricultural community in the inland Pacific Northwest (iPNW) United States. This study quantitatively predicts dust emissions from agroecological classes (AECs) of iPNW based on soil and land use types in response to climate change. The Wind Erosion Prediction System (WEPS) was used to simulate daily soil and PM10 (particulate matter ≤10 μm in aerodynamic diameter) loss at 29 meteorological stations across the iPNW. From 2009 to 2018, annual soil and PM10 loss decreased 1.18 and 0.05 kg m −2 yr −1, respectively. We presume that this decrease may be due to decreased wind speed, rather than other parameters like precipitation or solar radiation. St. John, WA had not only the highest annual soil loss but also the greatest mean wind speed and number of events with wind speeds >8 m/s. However, Lind, WA appeared to have greater soil surface erodibility in terms of greater rates of hourly soil and PM10 loss. Wind erosion occurred most frequently during March and April. The average maximum annual soil and PM10 loss in the grain‐fallow stable (24.7 and 0.63 kg/m 2, respectively) exceeded that of all other agroecosystems. This suggested that maintaining crop cover is critical for protecting the soil surface from erosion. Key Points: Annual soil and PM10 loss were simulated by the Wind Erosion Prediction System based on weather, and soil, land use types Annual soil and PM10 loss decreased 1.18 and 0.05 kg m −2 yr −1, respectively, from 2009 to 2018 Dust emission occurred most frequently during March and April